Geopolitical Trails for the Decolonization of Latina American Territorialities - Pérez Jiménez, César (2022)
The formation of geopolitics has emerged from the conquering vision of territories, subjectivities and natural resources, revealing the hegemonies of domination. In these world geopolitical traits, historically Latin America and its territories, its resources and its peoples have represented a territoriality object of exploitation and exclusion. It is the purpose of this conceptual cartographic analysis, to reason about the constitution and institution of the coloniality of territoriality as part of the hegemonic geopolitical agenda, and how it is oriented to reveal the challenges and challenges arising from the conjunctures that surround the region, on purpose to counteract the imperialist determination that falls on those disputed territories, considering the resistance of the peoples who have participated in the intercultural dialogues that emerged as part of an education and criticism of culture aimed at the decolonization of territorialities, particularly in these times that are moving towards a new normal.